2019
DOI: 10.1016/j.ijrobp.2018.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up on NRG Oncology RTOG 0915 (NCCTG N0927): A Randomized Phase 2 Study Comparing 2 Stereotactic Body Radiation Therapy Schedules for Medically Inoperable Patients With Stage I Peripheral Non-Small Cell Lung Cancer

Abstract: Purpose/Objective(s): To present long-term results of RTOG 0915/NCCTG N0927, a randomized lung stereotactic body radiotherapy (SBRT) trial of 34 Gy in 1 fraction versus 48 Gy in 4 fractions. Materials/Methods: This was a phase II multicenter study of medically inoperable non-small cell lung cancer patients with biopsy-proven peripheral T1 or T2 N0M0 tumors, with 1-year toxicity rates as primary endpoint and selected failure and survival outcomes as secondary endpoints. The study opened in September 2009 and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
162
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(171 citation statements)
references
References 10 publications
5
162
1
3
Order By: Relevance
“…According to previous studies with four fractions as well as in our study, ≥ grade 3 pneumonitis after CIRT was less frequent than after SBRT or PBT [ 7 , 13 , 21 , 22 ]. Even compared to single-fraction SBRT reported in the Radiation Therapy Oncology Group 0915 [ 23 ], single-fraction CIRT had fewer ≥ grade 2 respiratory toxicities (0% in the present study vs. 13% in single-fraction SBRT). A possible explanation is that CIRT reduces the surrounding lung dose compared to SBRT or PBT [ 24 , 25 ].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…According to previous studies with four fractions as well as in our study, ≥ grade 3 pneumonitis after CIRT was less frequent than after SBRT or PBT [ 7 , 13 , 21 , 22 ]. Even compared to single-fraction SBRT reported in the Radiation Therapy Oncology Group 0915 [ 23 ], single-fraction CIRT had fewer ≥ grade 2 respiratory toxicities (0% in the present study vs. 13% in single-fraction SBRT). A possible explanation is that CIRT reduces the surrounding lung dose compared to SBRT or PBT [ 24 , 25 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Demizu et al reported that CIRT reduces irradiated lung doses compared to PBT while maintaining equal coverage for lung tumors [ 25 ]. In fact, SBRT for early lung cancer is a good treatment option considering the OS and LC in a previous study [ 7 , 23 ], but CIRT may lead to low respiratory toxicities with good OS and LC due to the low irradiation volume compared to SBRT. In the present study, we did not find any factors for pneumonitis because there was no ≥grade 2 radiation pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…The ESTRO-ASTRO consensus group was unanimous in recommending SABR in a patient with stage I NSCLC referred by a surgeon because of operating room closures or delays (32). Their group also supported delivering SABR as a single fraction if the treating physician wished to reduce the number of visits in the early pandemic phase (25,26,32).…”
Section: Challenges During Covid19 Pandemicmentioning
confidence: 99%
“…Two recent randomized trials have indicated promising results when using a single-fraction SABR approach (one dose of 30-34 Gy), with similar toxicity and oncologic outcomes compared to a 3-fraction (60 Gy) regimen and a 4-fraction (48 Gy regimen) (25,26). During the COVID-19 pandemic, the singlefraction SABR approach has the advantage of reducing visits to radiotherapy departments down to only two: one visit for CT simulation, and one visit for treatment (25,26,32).…”
Section: Challenges During Covid19 Pandemicmentioning
confidence: 99%
“…Delivery of SABR in a single fraction is a potentially more convenient approach for patients, and the safety and efficacy of single-fraction SABR has been demonstrated for both early-stage NSCLC and pulmonary metastases [5] , [6] , [7] , [8] , [9] . However, clinical use of single-fraction SABR does not appear to be widespread, in part due to concerns about the accuracy of SABR delivery.…”
Section: Introductionmentioning
confidence: 99%